The benefits of role play in the development of drawing in preschool children - Bonilla-Sánchez, María del Rosario; García-Flores, Marco Antonio; Méndez-Balbuena, Ignacio; Silva-González, Jocelyn Guadalupe; Ramírez-Arroyo, Ernesto Vladimir (Frontiers in Psychology, 2022)
Objective The purpose of our study was to demonstrate the benefits of role play based on a Historical–Cultural perspective with the implementation of symbolic elements generated by the development of drawing of preschool children from suburban origin in a group of normal Mexican preschool children. We predict that the quality of the drawings will be improved after the preschoolers participate in such a role play program. Methods A pre-experimental study was carried out, with pre-test and post-test assessments. The drawings were assessed with quantitative (frequencies of the quality of the parameters) and qualitative (characteristics of the children's drawings) methods. The role play program was based on Elkonin's method, activity theory, and P. Ya Galperin's formation by stages of mental actions. The program encouraged the use of graphic signs and symbols, with the intention of representing situations, actions, objects, and/or contents. Twenty-six preschool children participated in our study. Results To know the effect of the role play program with symbolic elements on the drawing of preschool children, we performed a quantitative and qualitative analysis, a Wilcoxon test contrast between the initial and final assessment. Both analyses showed a significant increase in the scores in all the tasks with a medium–large effect size, being the largest “Pictograms” and “Drawing of the route”; and in the analysis of the qualitative parameters, specifically in “Maintains the objective,” a significant increase was found in all the tasks. Discussion Role play, being the main activity in preschool age, develops all aspects of the child's psychic life. The importance of role play in a preschool child makes it possible to work in the zone of proximal development with the regulatory function of language, with the planning, execution, and control of playful activity and, most importantly, with the use of various materials and perceptual-graphics tools. These findings showed an improvement in the development and complexity of the symbolic function in the drawings. Conclusion Role play, as a work methodology in preschool age, leads to the use of new meaning systems that prepare the child to carry out present and future complex symbolic actions.